Effectiveness of Sketch Engine for Language Learning as an Educational Tool for Improvement of Paraphrasing Skills of ESL/EFL Undergraduate Students: https://doi.org/10.5281/zenodo.16730128 - Summaira Sarfraz,; Nokhaiz Zahra, (Dialogue Social Science Review (DSSR), 2025)
This study aims to investigate the effectiveness of SkELL - Sketch Engine for Language Learning in terms of improving students’ paraphrasing skill using the three features of SkELL web interface, i.e., examples, word sketch and similar words. Paraphrasing skill is an under explored area in language learning which highly affects ESL/EFL students’ academic performance however, Pakistani students lack this skill as they encounter deficiency in vocabulary, comprehension, semantic and syntactical expertise. SkELL based activities utilizing word collocations, thesaurus and concordance, helped students overcome these problems. For the evaluation of the intervention of SkELL in teaching paraphrasing skill, exploratory sequential method was followed; a mixed method approach using a quasi- experimental approach for quantitative data collection and focus group interviews were conducted for qualitative data collection. Keck's taxonomy was adopted as a conceptual framework moreover, it was utilized as the rubric for evaluating paraphrasing skill, encompassing four types of paraphrasing: near copy, minimal revision, moderate revision, and substantial revision. For the quantitative data analysis IBM SPSS- 25 and for the qualitative data analysis MAXQDA-2022 were used. The Wilcoxon test result indicated a significant difference in the paraphrasing skill of students between the pre-test and post-test.